Perception of Social Media Information towards Retail Sector in Saudi Arabia - Merwa Abdulgadir, Alamin Ali (2016)
Social media has expedited unparalleled growth in human interaction in modern times. This new media has caught the attention of retails organizations, communities and individuals through their ability to facilitate the collaboration of virtual communities and to provide a productive environment for mutual sharing and interaction. The adoption of social media for retail sector worldwide is on the rise. Many retails & corporation today have official Facebook pages, Twitter accounts as well as retails blogs. All these are signs that social media has become a vital part of consumers’ daily lives as well as the day-to-day operations of retails organizations. The objective of this research is to explore into future trends in Saudi Arabia’s retail sector and to offer a detailed quantitative analysis of both past and future social media trends in the sector. This paper entails to cover on the various techniques that organizations especially in the retail sector put into consideration so as to gain from social media such as Twitter, Facebook, Instagram and YouTube among other platforms. The research will significantly trigger the retail sector in Saudi Arabia to use social media as a channel of communication as a result of essentiality of information as well as communication advancements and the increasing rate of internet usage.